ANALYSING SLANG LANGUAGE IN ONE SELECTED MOVIE AND ITS INFLUENCE ON CONVERSATION OF EFL LEARNERS - Devi Tania Maudy; Alin Herliyana Putri; Aldha Williyan (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2023)
This study aims to analyse the types of Back to the Outback movie slang used by college students in daily conversation. This study was written using qualitative methods by the researchers. Slang was analysed using Allan and Burridge's theory in this study. To analyse the slang words, the researcher watched to the movie's dialogue and subtitles and categorizes each slang according to the theory used. Following that, the researcher gathered some information from the student questionnaire results. Researchers discovered 30 slang words as a result of their research. There are 30 slang terms divided into four categories. There are 15 slang in the Fresh and Creative type, 8 in Flippant, 5 in Imitative, and 2 in Clipping. According to the study's findings, the slang used was more prevalent in the Fresh and Creative types, with 15 data for this type. Furthermore, students are more likely to use slang in their daily conversations for fresh and creative types. It can be concluded that movies are very effective at providing language transfer to anyone wishing to learn English.